A comparative study of pregnancy complications and birth outcomes in very advanced maternal age women: a retrospective cohort analysis - Godara, Juhi; Vasanth, Uma; Waheed, Seema; Makhdoom, Tazeen; Binashoor, Amina Karim; AlSayari, Saba Yehya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: There has been a noted increment in the number of women having children at a very advanced maternal age (VAMA), in the recent decades. This changing trend raises concerns regarding the risks involved and the associated complications with pregnancy occurring in both the mother and the newborn. The associated complications include stillbirths, placental problems, higher risks of cesarean sections and gestational diabetes. Existing research on the correlative aspects of pregnancy outcomes and VAMA, however have shown contradicting results. Hence, the findings of the same remain debatable. Methods: This was a hospital-based retrospective cohort study, conducted on 100 women delivering between the years 2018 and 2023. The participants were classified into two different groups: group I- low-risk women, including 50 pregnant females of age less than 35 years and group II- VAMA females, 50 pregnant females of age up to 45 years. Results: Women falling in the category of VAMA reported an increased rate of complications; most of these were gestational diabetes and hypertensive disorders. With this evidence, pregnancy results for advanced-aged women ought to be enhanced using targeted care and greater alertness in antenatal checkups. Conclusions: More attention should be paid to women exposed to VAMA during pregnancy. Better education and timely intervention are critical in preventing complications and contributing to healthier pregnancies in this group.